1993
DOI: 10.1182/blood.v82.4.1110.1110
|View full text |Cite
|
Sign up to set email alerts
|

Human FLT3/FLK2 gene: cDNA cloning and expression in hematopoietic cells

Abstract: The human FLT3 cDNA was cloned from a pre-B cell line and characterized. The deduced amino acid sequence shows that FLT3 codes for a receptor-type tyrosine kinase of 993 residues, presenting a strong similarity with the corresponding mouse FLT3/FLK2 protein as well as with the receptors for colony-stimulating factor 1 (CSF1R/FMS) and steel locus factor (SLFR/KIT). An analysis of the expression of the gene using amplification of reverse transcribed FLT3 mRNA by polymerase chain reaction shows that FLT3 is expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
134
1
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 299 publications
(138 citation statements)
references
References 32 publications
1
134
1
2
Order By: Relevance
“…In addition, expression of FLT3 was also reported in many different haemopoietic cell lines including, in particular, pro/pre-B cell lines (Birg et al, 1992;Da Silva et al, 1994;Meierhoff et al, 1995). In haematological malignancies, recent clinical studies showed that FLT3 mRNA was expressed in the majority of patients with B-lineage acute lymphoblastic leukaemia (ALL) and acute myeloid leukaemia (AML), especially those containing a monocytic component (Birg et al, 1992;Rosnet et al, 1993;Brasel et al, 1995;Meierhoff et al, 1995;Drexler, 1996).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, expression of FLT3 was also reported in many different haemopoietic cell lines including, in particular, pro/pre-B cell lines (Birg et al, 1992;Da Silva et al, 1994;Meierhoff et al, 1995). In haematological malignancies, recent clinical studies showed that FLT3 mRNA was expressed in the majority of patients with B-lineage acute lymphoblastic leukaemia (ALL) and acute myeloid leukaemia (AML), especially those containing a monocytic component (Birg et al, 1992;Rosnet et al, 1993;Brasel et al, 1995;Meierhoff et al, 1995;Drexler, 1996).…”
mentioning
confidence: 99%
“…Fms-like tyrosine kinase 3 (FLT3), also referred to as fetal liver kinase 2 (flk2) or stem cell tyrosine kinase 1 (STK-1) (Lyman et al, 1993b;Rosnet et al, 1993;Small et al, 1994), located on chromosome 13q12 (Rosnet et al, 1991b), is a class III receptor tyrosine kinase (RTK), along with KIT, FMS and platelet-derived growth-factor receptor (PDGFR) (Matthews et al, 1991;Rosnet et al, 1991a, b;Agnes et al, 1994;Meierhoff et al, 1995), which play a central role in haemopoiesis together with corresponding ligands (Brasel et al, 1995;Carow et al, 1996;Drexler, 1996). RTKs are composed of five immunoglobulin-like subdomains in the extracellular region, a single transmembrane (TM) domain, a juxtamembrane (JM) domain, two intracellular tyrosine kinase domains (TK1 and TK2) divided by a kinase insert (KI) domain, and a C-terminal domain.…”
mentioning
confidence: 99%
See 3 more Smart Citations